PROFIL RUMAH TANGGA YANG MENGGUNAKAN GARAM BERIODIUM: STUDI KASUS DI ENAM DESA DI JAWA TIMUR - Astuti Lamid; Tjetjep S. Hidayat; Arnelia Arnelia; Nurfi Afriansyah; Djoko Susanto (Persagi, 1994)
PROFIL RUMAH TANGGA YANG MENGGUNAKAN GARAM BERIODIUM: STUDI KASUS DI ENAM DESA DI JAWA TIMUR